Las relaciones familiares y su influencia en los aprendizajes significativos, en niños y niñas de los subniveles, básico, medio, superior de la escuela fiscal mixta Elvia Bélgica Jiménez González del barrio Rumizhitana parroquia Malacatos cantón y provincia de Loja. Año lectivo 2012-2013 - Armijos Yunga, Sandra Janeth (2014)
This research entitled: FAMILY RELATIONSHIPS AND SIGNIFICANT INFLUENCE ON LEARNING IN CHILDREN OF sublevels , BASIC , MEDIUM, HIGH SCHOOL OF THE JOINT FISCAL ELVIA JIMENEZ GONZALEZ DEL BARRIO BELGIUM RUMIZHITANA CANTON AND PARISH Malacatos Loja province . SCHOOL YEAR 2012-2013. With the overall objective : In determining the level of influence between family relations , and advancement of meaningful learning in children from the Fiscal School Elvia Gonzalez Jimenez Belgium, 2012-2013 . scientific method , descriptive method , synthetic method , deductive, inductive method , descriptive method , literature method and statistical method: the following methods are used. The technique used was : a survey of teachers, parents and students of the institution. To determine the influence of the significant learning of children in households in which nine teachers involved ; 20 parents and 36 students Elvia Gonzalez Jimenez Belgium Rumizhitana School district . The applied surveys showed high percentages of poor family relationships that exist in the institution, as well as low meaningful learning in them , once analyzed all the problems we conclude that family relationships school Elvia Belgium Jimenez Gonzalez are not suitable for the reason that children fail to acquire a good meaningful learning. It is therefore recommended to parents who have a duty to ensure their children give them the necessary support to achieve progress in obtaining a significant learning support